Gut and vessel alterations induced by mesenteric ischaemia/reperfusion in rats - Nosál'ová, V; Sotníková, R; Mihalová, D; Navarová, J (Central European journal of public health, 2004)
A rat model of transient occlusion of the superior mesenteric artery was used to study the intestinal and vascular injury induced by ischaemia/ reperfusion (I/R). A pronounced intestinal injury was observed, ranging from hyperaemia to severe haemorrhagic necrosis and bleeding. The length of the damaged intestinal segments reached 58.6% of the small intestine with a decrease of the wet weight in the I/R group. Sham operation resulted in 100% survival, I/R decreased survival to 40% after 24 h. Following I/R a significant increase of vascular permeability was observed in the small intestine. Gamma-glutamyl transpeptidase activity decreased aborally in sham operated rats and I/R reduced it further in all parts of the small intestine. I/R resulted in damaged endothelium-dependent relaxation of mesenteric artery rings. This was manifested by decreased maximal responses of arterial preparations to acetylcholine as well as decreased pD2 values. The results confirmed and specified the presumed effect of I/R on the small intestine and on vascular functions.
Keywords: Reactive Oxygen Species; krysa rodu Rattus; mužské pohlaví; Male; Intestines; Mesenteric Arteries; analýza rozptylu; reperfuzní poškození; reaktivní formy kyslíku; modely nemocí na zvířatech; Rats; potkani Wistar; Ischemia; Animals; ischemie; Analysis of Variance; střeva; zvířata; Rats, Wistar; Disease Models, Animal; arteriae mesentericae; Reperfusion Injury